2014
DOI: 10.1155/2014/976321
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Cord Blood Therapy for Infantile Cerebral Palsy: From Bench to Bedside

Abstract: About 17 million people worldwide live with cerebral palsy, the most common disability in childhood, with hypoxic-ischemic encephalopathy, preterm birth, and low birth weight being the most important risk factors. This review will focus on recent developments in cell therapy for infantile cerebral palsy by transplantation of autologous umbilical cord blood. There are only 4 publications available at present; however, the observations made along with experimental data in vivo and in vitro may be of utmost impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Studies related to the use of hESC therapy in patients with CP are few however; the use of cord stem cells in CP patients has been evaluated for efficacy in studies from the past. Transplantation of cord stem cells in a 2.5 year old boy with CP demonstrated significant improvement in motor function at week 4 of therapy, normal EEG and partial recovery from vision loss at week 7 of therapy [ 19 ]. Another study examining the efficacy of stem cells in a 6 year old CP patient showed significant improvement in motor function within 6 months of therapy and also showed cognitive, speech, and sensory improvements [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies related to the use of hESC therapy in patients with CP are few however; the use of cord stem cells in CP patients has been evaluated for efficacy in studies from the past. Transplantation of cord stem cells in a 2.5 year old boy with CP demonstrated significant improvement in motor function at week 4 of therapy, normal EEG and partial recovery from vision loss at week 7 of therapy [ 19 ]. Another study examining the efficacy of stem cells in a 6 year old CP patient showed significant improvement in motor function within 6 months of therapy and also showed cognitive, speech, and sensory improvements [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We report a rare case of traumatic neonatal ischemic stroke with hemiplegic cerebral palsy caused by functional cephalopelvic disproportion and parietal head depression due to a “long pelvis” of the mother [ 2 ] that was treated with autologous cord blood mononuclear cells [ 6 ]. The ischemic stroke resulted from a traumatic occlusion of a penetrating thalamostriatal tributary of the left middle cerebral artery supplying the white matter beyond the basal ganglia, a unique feature of the developing brain [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, neurotrophic (e.g., BDNF, VEGF), synaptotrophic (e.g., NGF), anti-inflammatory (e.g., Il-6, Il-8, and Il-10), antigliotic (e.g., Cx43), antiapoptotic, and proangiogenic neuroregenerative effects are entrained resulting in significant functional neuroregeneration [ 12 16 ]. The beneficial effects of cord blood mononuclear cells observed after acute brain damage caused by hypoxic-ischemia include reduced spastic paresis and recovery of gross motor function, fine motor coordination, muscle strength, somatosensory cortical processing, and, as observed in children, recovery of cognition, vision, and active and receptive speech competence [ 4 , 6 , 9 , 11 , 13 ]. To what extent these processes may be involved in neuroregeneration after late transplantation of autologous cord blood mononuclear cells as in the present case remains to be established in further systematic clinical research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UCB components involved in cell therapy research are shown in Table 1. Compared with other types of stem cells, those from the UCB have advantages in terms of CP treatment safety and efficacy 22,25,34 , ethics 35 , non-neoplastic proliferation, accessibility, ease of preservation 36 , and regulation of immune responses 25 , based on findings in animal models and clinical trials 28,[37][38][39][40] . In animal studies, UCB cell therapy has made substantial progress (migration to sites 41 , improvement of functional loss 42 , and prevention of white matter damage 43 ).…”
Section: Ucb Composition Selection and Treatment Mechanismmentioning
confidence: 99%